EFFICIENCY OF MICROORGANISM IN YARDLONG BEAN (Vigna sesquipedalis (L.) Fruw.) PRODUCTION IN NORTHERN THAILAND - Dechjirarattanasiri , Chatprawee; Inthasan, Jiraporn (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
Biofertilizer is one of the substances that consist of living microorganismssuch as bacterial, actinomyces and fungi. These could be helped plants increasing essential elements and encourage growth. Rhizobium are a type of bacteria that conformation a symbiotic relationship with legume plant. This bacteria not only fix nitrogen but also are involved in increasing nutrient availability and regulating plant growth hormones. Mycorrhiza fungi are help plant by enhancing absorption and increasing uptake of nutrients. These beneficial of rhizobium and mycorrhiza bring this study to chose for checking the influence of yardlong bean production in Chiangmai, Thailand from June to November 2022. Randomized Completely Block Design (RCBD) with 4 treatments 4 replications as followed treatment 1) the control (without biofertilizer), treatment 2) rhizobium (R), treatment 3) mycorrhiza (M), and treatment 4) rhizobium + mycorrhiza (R + M) was laid out in this experiment. The data indicated that combining between rhizobium and mycorrhiza caused the highest average weight per pod (23.1 g) and pod length (53.4 cm), yardlong bean quality as well as vitamin C, total Chlorophyll and total dietary fiber at 20.2 mg 100g-1, 0.20 μg g-1 and 2.7 mg 100g-1 respectively. This biofertilizer management methods provided the higher nitrogen, phosphorus, potassium, calcium, magnesium iron and zinc contents of bean comparing with control treatment. Remarkably, mixed rhizobium and mycorrhiza elevated the highest yield of yardlong bean (369 kg ha-1)